Klastry jako forma struktury sieciowej w polityce regionalnej - Juchniewicz, Małgorzata (Clusters as a Form of Network Structure in the Regional Policy, 2009)
The frequency and intensity of network links, including clusters, is of significant importance to increase competitiveness of the region and businesses located in it. Regional policy can create conditions and encourage the creation of clusters' initiatives. Further, development of clusters will depend on the participants' perception of visible benefits of their operation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 617-625